2018
DOI: 10.1136/bjophthalmol-2018-312649
|View full text |Cite
|
Sign up to set email alerts
|

Photophobia and sensations of dryness in patients with migraine occur independent of baseline tear volume and improve following botulinum toxin A injections

Abstract: Background: To evaluate the efficacy of botulinum toxin A (BoNT-A) in reducing photophobia and dry eye symptoms in individuals with chronic migraine. Additionally, we aimed to evaluate tear film volume as a potential contributor to symptoms in these patients. Methods: Retrospective review of seventy-six patients who received BoNT-A for chronic migraine (CM) between August 23, 2017 and December 13, 2017 at the Miami Veterans Affairs Medical Center Neurotoxin Clinic. Demographic data and all co-morbidities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“… 41 In a retrospective cross-sectional study of 117 individuals with chronic migraine (≥15 headache days/month), 80% rated their photophobia (via 0–10 NRS) as severe (a score of ≥7/10; mean 7.91 ± 2.05). 42 Together, the data demonstrate that photophobia is a feature of both dry eye and migraine. The presence of photophobia in both diseases has implications for shared pathophysiology and treatments as discussed later in the review.…”
Section: Clinical Associations Between Dry Eye and Migrainementioning
confidence: 80%
“… 41 In a retrospective cross-sectional study of 117 individuals with chronic migraine (≥15 headache days/month), 80% rated their photophobia (via 0–10 NRS) as severe (a score of ≥7/10; mean 7.91 ± 2.05). 42 Together, the data demonstrate that photophobia is a feature of both dry eye and migraine. The presence of photophobia in both diseases has implications for shared pathophysiology and treatments as discussed later in the review.…”
Section: Clinical Associations Between Dry Eye and Migrainementioning
confidence: 80%
“…One month was chosen as the follow-up timepoint as a previous study had detected significant reductions in photophobia and DE symptoms in individuals with chronic migraine about 1 month after injection with onabotulinumtoxinA. 16
Fig. 1 Injection Sites for Botulinum Toxin A Using a Modified Migraine Protocol.
…”
Section: Resultsmentioning
confidence: 99%
“…In the arena of neuropathic-like DE symptoms, prior studies have shown that BoNT-A injections improved photophobia and DE symptoms in individuals with underlying chronic migraine, independent of an improvement in tear film volume. 15 , 16 These improvements were thus hypothesized to be driven by modulation of vascular and neural pathways shared by migraine pain, photophobia, and DE symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 62 individuals with chronic migraine treated with BoNT-A (100–150 units every 3 months based on migraine protocol), BoNT-A not only decreased migraine pain 4–6 weeks post treatment compared to pretreatment but also interictal photophobia (3.4 ± 2.5 vs. 4.9 ± 3.0; p < 0.001) and overall light sensitivity (assessed using the Visual Light Symptom Questionnaire [VLSQ]-8 [ 110 ]: 27.7 ± 6.5 vs. 29.8 ± 5.1; p = 0.002). Responses to the questions in the VLSQ-8 questionnaire revealed improvements in frequency of glare (2.9 ± 1.3 vs. 3.4 ± 0.86; p = 0.001), light sensitivity from flickering lights or bright colors (3.1 ± 1.3 vs. 3.7 ± 1.0; p = 0.004), and severity of worst period of photophobia (3.7 ± 1.0 vs. 4.2 ± 0.88; p = 0.001) in the past month [ 111 ]. Interestingly, these findings were independent of tear volume, again suggesting that ocular surface findings do not drive ocular surface pain in many individuals.…”
Section: Approach To Treatmentmentioning
confidence: 99%